PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD NEGERI 4 MAKERUH - Reni Sinarti; Lazim N Lazim N; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Use of Make a Match Model in Improving Science Learning of Grade V Students of SD Negeri 4 Makeruh. The purpose of this study is to describe the steps of using make a match model, improving science learning of grade 5 students of SD Negeri 4 Makeruh through the use of make a match model. This research is a Classroom Action Research. The study was conducted in three consisting of planning, implementation, observation, and reflection. The subjects of this study were the students of grade V of SD Negeri 4 Makeruh which consisted of 30 students consisting of 12 men and 18 women. The results showed that the use of make a match model can improve science learning of grade 5 students of SD Negeri 4 Makeruh.Keywords: Make a Match, Science Lesson